Factors associated with HIV testing among patients seeking emergent injury care in Kigali, Rwanda - Aly Beeman; Catalina Gonzalez Marques; Oliver Y. Tang; Chantal Uwamahoro; Spandana Jarmale; Zeta Mutabazi; Vincent Ndebwanimana; Doris Uwamahoro; Mediatrice Niyonsaba; Andrew Stephen; Adam R. Aluisio (African Journal of Emergency Medicine, 2022)
Introduction: Emergency centres (ECs) can be important access points for HIV testing. In Rwanda, one in eight people with HIV are unaware of their infection status, which impedes epidemic control. This could be addressed via increased testing. This cross-sectional study evaluated factors associated with EC-based HIV testing among injured patients at the Centre Hospitalier Universitaire de Kigali (CHUK), in Kigali, Rwanda. Methods: Adult injury patients were prospectively enrolled between January-June 2020. Trained study personnel collected data on demographics, injury aspects, treatments, HIV testing, and disposition. The primary outcome was the completion of EC-based HIV testing. Differences between those receiving and those not receiving testing were assessed. Regression models yielding adjusted odds ratios with associated 95% confidence intervals (CI) were calculated to quantify magnitudes of effect. Results: Among 579 patients, the majority were under 45 years of age (78.1%) and male (74.4%). The most common mechanism of injury was road traffic accidents (50.3%). EC discharge occurred in 54.4% of cases. HIV testing was performed in 221 (38.2%) cases, of which 5.9% had a positive result. HIV testing was more likely among males (aOR=1.69, 95% CI: 1.02–2.78; p=0.04), cases transported by prehospital services (aOR=2.07, 95% CI: 1.28-3.35; p=0.003) and those receiving surgical consultation (aOR=3.13, 95% CI: 1.99-4.94; p<0.001). Cases with lower acuity were less likely to be tested (OR=0.70, 95% CI: 0.55-0.90; p=0.004), as were those discharged (OR=0.28, 95% CI: 0.18-0.43; p<0.001). Conclusion: In the population studied, most patients did not undergo HIV testing. EC-based physician directed testing was more likely among male patients and patients with greater care needs. These results may inform approaches to increase EC-based testing services in Rwanda and other similar settings with high HIV burdens.